ZoneZoom: Map Navigation for Smartphones with Recursive View Segmentation - Robbins, Daniel; Cutrell, Ed; Sarin, Raman; Horvitz, Eric (AVI '04: Proceedings of the working conference on Advanced visual interfaces, 2004)
ZoneZoom is an input technique that lets users traverse large information spaces on smartphones. Our technique ZoneZoom, segments a given view of an information space into nine sub-segments, each of which is mapped to a key on the number keypad of the smartphone. This segmentation can be hand-crafted by the information space author or dynamically created at run-time. ZoneZoom supports “spring-loaded” view shifting which allows users to easily “glance” at nearby areas and then quickly return to their current view. Our ZoneZoom technique lets users gain an overview and compare information from different parts of a dataset. SmartPhlow is an optimized application for browsing a map of local-area road traffic conditions.